2012
DOI: 10.1371/journal.pone.0043980
|View full text |Cite
|
Sign up to set email alerts
|

The Minimal Deneddylase Core of the COP9 Signalosome Excludes the Csn6 MPN− Domain

Abstract: The COP9 signalosome (CSN) is a eukaryotic protein complex, which regulates a wide range of biological processes mainly through modulating the cullin ubiquitin E3 ligases in the ubiquitin-proteasome pathway. The CSN possesses a highly conserved deneddylase activity that centers at the JAMM motif of the Csn5 subunit but requires other subunits in a complex assembly. The classic CSN is composed of 8 subunits (Csn1–8), yet in several Ascomycota, the complex is smaller and lacks orthologs for a few CSN subunits, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 59 publications
2
38
0
Order By: Relevance
“…The C-terminal half of CSN6 is required for its interaction with both CSN4 and CSN7, leaving its MPN domain available for interaction with CSN5. How this fits with a recent report where the MPN domain is not essential for CSN5-mediated deneddylation is not clear (35). Our preparation of a heterotrimer of CSN4, CSN6, and CSN7 may best fit with earlier findings that both Arabidopsis and Drosophila CSN5 appeared to be nonessential for complex formation (18,19), in contrast to another report which showed that CSN5 does appear to be essential for complex formation (14).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The C-terminal half of CSN6 is required for its interaction with both CSN4 and CSN7, leaving its MPN domain available for interaction with CSN5. How this fits with a recent report where the MPN domain is not essential for CSN5-mediated deneddylation is not clear (35). Our preparation of a heterotrimer of CSN4, CSN6, and CSN7 may best fit with earlier findings that both Arabidopsis and Drosophila CSN5 appeared to be nonessential for complex formation (18,19), in contrast to another report which showed that CSN5 does appear to be essential for complex formation (14).…”
Section: Discussionsupporting
confidence: 80%
“…CSN6 contains an N-terminal MPN domain and a newly identified S6CD domain in the carboxyl half of the protein (35). We first employed the yeast two-hybrid assay to determine which domains of CSN6 contribute to its interaction with CSN7.…”
Section: Mpn Domain Of Csn6 Is Not Required For Csn4-6-7mentioning
confidence: 99%
“…Recently, Pick et al (24) showed that purified budding yeast CSN complex, which lacks Csn8, can effectively deneddylate human cullins, indicating that Csn8 is probably not required for the deneddylase activity. We believe that the deneddylation defect in Csn8 h cells is most likely due to decreased CSN level (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Csn8 is absent from the CSN assembly of Caenorhabditis elegans and some of the fungal species (22)(23)(24)(25)(26). Meanwhile, it has become increasingly clear that the functions of the eight CSN subunits are different because ablation or knockdown of different CSN subunit can lead to different functional consequences.…”
mentioning
confidence: 99%
“…The budding yeast Saccharomyces cerevisiae, for instance, seems to have evolved a particularly divergent CSN. The ScCSN (S. cerevisiae CSN) is composed of six subunits, four PCI subunits (Csn9, Csn10/Rri2, Csn11/Pci8, Rpn5), one MPN subunit (Csn5/Rri1) and Csi1, a diverged homologue of Csn6 which does not contain recognizable domains [18][19][20][21][22].Whereas CSN is essential for the development of organisms as different as plants (A. thaliana) and animals (Drosophila melanogaster; Caenorhabditis elegans; mouse and human), budding yeast can survive without a CSN. Indeed, deletions of CSN5 and CSN9 genes show some increase in pheromone sensitivity and mating efficiency but do not affect yeast viability [20].…”
Section: Introductionmentioning
confidence: 99%